A conserved ATG2 binding site in WIPI4 and yeast Hsv2 is disrupted by mutations causing β-propeller protein-associated neurodegeneration. Issue 1 (9th August 2021) - Bueno-Arribas, Miranda; Blanca, Irene; Cruz-Cuevas, Celia; Escalante, Ricardo; Navas, María-Angeles; Vincent, Olivier
Abstract: PROPPINs are phosphoinositide-binding β-propeller proteins that mediate membrane recruitment of other proteins and are involved in different membrane remodeling processes. The main role of PROPPINs is their function in autophagy, where they act at different steps in phagophore formation. The human PROPPIN WIPI4 ( WDR45 ) forms a complex with ATG2 involved in phagophore elongation, and mutations in this gene cause β-propeller protein-associated neurodegeneration (BPAN). The yeast functional counterpart of WIPI4 is Atg18, although its closest sequence homolog is another member of the PROPPIN family, Hsv2, whose function remains largely undefined. Here, we provide evidence that Hsv2, like WIPI4 and Atg18, interacts with Atg2. We show that Hsv2 and a pool of Atg2 colocalize on endosomes under basal conditions and at the pre-autophagosomal structure (PAS) upon autophagy induction. We further show that Hsv2 drives the recruitment of Atg2 to endosomes while Atg2 mediates Hsv2 recruitment to the PAS. HSV2 overexpression results in mis-sorting and secretion of carboxypeptidase CPY, suggesting that the endosomal function of this protein is related to the endosome-to-Golgi recycling pathway. Furthermore, we show that the Atg2 binding site is conserved in Hsv2 and WIPI4 but not in Atg18. Notably, two WIPI4 residues involved in ATG2 binding are mutated in patients with BPAN, and there is a correlation between the inhibitory effect of these mutations on ATG2 binding and the severity of the disease.